Sociedad, derecho y educación: la necesidad de formación jurídica para el sostenimiento de la sociedad - Briceño Medina, Enrique Miguel (2023)
This paper deals with the necessary relationship between law, society and education, pointing out the essential need for legal training for the maintenance and development of society. In this line, the work begins by identifying the relationship between society, law and education, to then analyze the role that law and education play in the social environment. Finally, a simple training proposal is outlined, pointing out some basic legal concepts, referring to some of the most important legal institutions, and then pointing out the main positive norms that must be known by citizens, all in order to guarantee integration and society development.